PLANKTON ABUNDANCE AND WATER QUALITY PROFILE OF VANNAMEI SHRIMP (Litopenaeus vannamei) FARMING INTENSIVE SYSTEM - Suprakto, Bambang; Bintari, Yunia Karisma; Aulia, Deni; Rizky, Putri Nurhanida; Wartini, Sri (Politeknik Kelautan dan Perikanan Dumai, 2024)
The vannamei shrimp (Litopenaeus vannamei) is one of the most popular shrimp species, widely cultivated throughout Indonesia. This species has several advantages, including rapid growth, the ability to be cultivated at high densities in intensive systems, and resilience to environmental changes. The presence of plankton and the quality of water in the cultivation medium significantly affect the growth and survival of vannamei shrimp. This study aims to evaluate plankton abundance and the dynamics of water quality in intensive vannamei shrimp farming. The research was conducted at two intensive vannamei shrimp farms in East Java with shrimp aged between 1 and 60 days. Water quality measurements were taken directly from the cultivation ponds (salinity, pH, and dissolved oxygen) and in the laboratory (ammonia, nitrite, phosphate, alkalinity, and total organic content). The average abundance of plankton in the intensive vannamei shrimp farming medium ranged from 190 x 10³ to 960 x 10³ individuals/mL, consisting of four groups: green algae, diatoms, dinoflagellates, and blue-green algae. Green algae were the most abundant group, making up 69.9% to 71.9%, while diatoms were the least abundant at 1.9% to 3.0%. In intensive vannamei shrimp farming, the salinity of the cultivation medium ranged from 16 to 35 ppt, pH from 7.5 to 9.0, dissolved oxygen from 3.2 to 5.7 mg/L, and temperature from 28.0 to 31.3°C. The water chemistry parameters measured were ammonia, nitrite, phosphate, alkalinity, and total organic content, with respective ranges of 0.001–0.030 mg/L, 0.05–1.00 mg/L, 0.25–3.00 mg/L, 104–232 mg/L, and 27–131 mg/L. The dynamics of water quality remained within the optimal range for vannamei shrimp farming, as outlined in Regulation KP Number 75 of 2016 regarding general guidelines for the rearing of tiger shrimp and vannamei shrimp.